The Role of Requests in the Criminal Case at the Trial Stage - Jasim, Tabarek; Al-Shamry, Kazem (Journal of Legal Sciences, 2023)
The trial stage is one of the important stages in the criminal case, which aims to assess the weight of the evidence, whether it is in the interest of the accused or against his interest. When the subject court presents the evaluation of the evidence, it presents it in terms of its value in proof. Therefore, the trial procedures guarantee to the litigants, especially the accused, many guarantees, including the right to defense and to express the requests that the legislator allowed them to make, and the judge is not bound by the requests of the litigants. He is free to deny the evidence and is not obligated to include in the reasons for his ruling all the evidence that was presented during the session. Rather, he is only obligated to state the evidence on which he built his conviction or justifies that abstention.